Formulasi dan Optimasi Basis Gel HPMC (Hidroxy Propyl Methyl Cellulose) dengan Berbagai Variasi Konsentrasi (Journal of Tropical Pharmacy and Chemistry, 2015)
Ideal gel formulation can be obtained by formulating some kind of gelling material, but the most important thing to note is the selection of a gelling agent. HPMC (Hidroxy Propyl Methyl Cellulose) is a gelling agent that is commonly used in the production of cosmetics and drugs, because it can producea gel that is clear, easily soluble in water, and has a low toxicity. This study aimed to obtain the concentration of HPMC as a gelling agent that has the physical stability in accordance with the stipulated requirements. Gel formulations made with HPMC concentration variation of 3%, 5% and 7%, further evaluation of physical properties include organoleptic test, homogeneity, dispersive power, pH, and viscosity. Evaluation gel base done for 3 weeks. The results of stability tests show the base gel with a concentration of 7% HPMC has a good standard for viscosity, pH, dispersive power, homogeneity and organoleptic.